2001
DOI: 10.1080/00071660120088371
|View full text |Cite
|
Sign up to set email alerts
|

Divergent selection for shape of growth curve in Japanese quail. 1. Responses in growth parameters and food conversion

Abstract: 1. HG and LG quail lines selected for high and low relative weight gain between 11 and 28 d of age (RG11-28), respectively, and an unselected C line were compared. Mature body weight of both selected lines was held at that of the C line. Progeny of generation 6 were used for analysis. 2. Divergent selection for RG11-28 brought about opposite changes in the growth rates shortly after hatching. 3. Parameters of the Richards function were used to describe the growth curve. The largest differences between HG and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 18 publications
11
35
1
Order By: Relevance
“…In that case, the possibility to change the shape of the growth curve while keeping mature weight constant was assumed. This approach is in accordance with the finding of Hyá nková et al (2001), as mentioned before.…”
Section: Definition Of Traits Characterising the Growth Potential Of supporting
confidence: 91%
See 1 more Smart Citation
“…In that case, the possibility to change the shape of the growth curve while keeping mature weight constant was assumed. This approach is in accordance with the finding of Hyá nková et al (2001), as mentioned before.…”
Section: Definition Of Traits Characterising the Growth Potential Of supporting
confidence: 91%
“…Current long-term selection experiments with the Japanese quail have shown that it is possible to change the shape of the growth curve, keeping mature weight (asymptotic weight) nearly constant (Hyá nková et al, 2001). However, according to these authors, mature weight must be a selection criterion next to growth rate to achieve this result.…”
Section: Definition Of Traits Characterising the Growth Potential Of mentioning
confidence: 99%
“…When the Richards model was used to describe the growth curve, the W i /W f ratio is preferred to m parameter to compare the shape of the growth curve of different sex or lines (Hyankova et al, 1997(Hyankova et al, , 2001). Logistic and Gompertz functions have a fixed point of inflection at about 50 and 37% of the asymptote, respectively (Aggrey, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis can also identify relations between growth curve parameters and important production and reproduction traits (e.g. de Torre et al, 1992;Menchaca et al, 1996;Hyánková et al, 2001). Frequently used are also allometric models (e.g.…”
mentioning
confidence: 99%